Aerodynamic Characteristics of a Rectangular Wing Using Non-LinearVortex Ring Method - Anmar Hamid Ali (Journal of Engineering, 2017)
The aerodynamic characteristics of general three-dimensional rectangular wings are considered using non-linear interaction between two-dimensional viscous-inviscid panel method and vortex ring method. The potential flow of a two-dimensional airfoil by the pioneering Hess & Smith method was used with viscous laminar, transition and turbulent boundary layer to solve flow about complex configuration of airfoils including stalling effect. Viterna method was used to extend the aerodynamic characteristics of the specified airfoil to high angles of attacks. A modified vortex ring method was used to find the circulation values along span wise direction of the wing and then interacted with sectional circulation obtained by Kutta-Joukowsky theorem of the airfoil. The method is simple and based mainly on iterative procedure to find the wings post stall aerodynamic results. Parametric investigation was considered to give the best performance and results for the rectangular wings. Wing of NACA 0012 cross sectional airfoil was studied and compared with published experimental data for different speeds and angle of attacks. Pressure, skin friction, lift, drag, and pitching moment coefficients are presented and compared good with experimental data. The present method shows simple, quick and accurate results for rectangular wings of different cross-section airfoils.